Stent-retriever induces more endothelial damage than direct aspiration in endovascular therapy for acute ischemic stroke. (3rd October 2022) - Taha, A; Bobi, J; Hund, H; Van Noorden, K; Stam, M; Raben, J D; Van Doormaal, P J; Duncker, D J; Van Der Lugt, A; Van Es, A C G M; Dippel, D W J; Van Beusekom, H M M
Abstract: Background: Mechanical arterial recanalization is increasingly used to treat acute ischemic stroke. Known to inflict vascular injury, it might affect pro-thrombotic character and healing patterns. Stent-retriever thrombectomy (SR) and direct aspiration (DA) are both used for acute recanalization and not only lead to endothelial denudation, but also to platelet activation and local formation of microthrombi, potentially adding to the risk of distal embolization. Purpose: We aimed to quantify and characterize endovascular damage, microthrombus formation, and vascular healing following SR and DA in a swine model of arterial thrombo-embolic occlusion. Methods: Aged autologous thrombi, created under flow, were used to occlude swine extracranial arteries for two hours to mimic a thrombo-embolic occlusion. Arteries were randomized to SR, DA, or control (C). Injury was assessed acutely (SR n=8; DA n=7; C n=4), and at 3 days follow-up (SR n=8; DA n=7; C n=4) using Evans Blue (EB) dye-exclusion-testing to quantify injury, expressed as %EB-area in the treated area. Scanning electron microscopy (SEM) was used to characterize vascular injury and presence of microthrombi (<100 μm). Data are given as mean±SD or median (min-max). Results: Regression analysis for EB-area (ANOVA p<0.001; Adj. R 2 =0.5) showed that SR induced more damage than DA (p=0.001). Both showed partial healing at 3 days (p<0.01) (Table 1). Only for DA, did more attempts lead to an increased EB-area (p=0.016), as for SR one attempt already resulted in almost complete denudation. For both SR and DA, SEM of acute injury showed endothelial denudation, microthrombi, and adhesion of leukocytes and activated platelets (Fig. 1A–C). At three days, SEM showed partial re-endothelialization with increased surface folds as a sign of endothelial activation (Fig. 1D). Microthrombi/cm 2 decreased significantly from 7 (2–17) acutely to 1 (0–4) at 3 days (p<0.001). Conclusions: Stent-retrievers induce more endothelial damage than direct aspiration. Both treatments yield microthrombi, platelet activation and leukocyte adhesion. After three days, the endothelium is significantly, but only partially recovered. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): We acknowledge the support of the Netherlands Cardiovascular Research Initiative which is supported by the Dutch Heart Foundation (CVON2015-01: CONTRAST), the support of the Brain Foundation Netherlands (HA2015.01.06), and the support of Health∼Holland, Top Sector Life Sciences & Health (LSHM17016), Stryker, Medtronic and Cerenovus. The collaboration project is additionally financed by the Ministry of Economic Affairs by means of the PPP Allowance made available by the Top Sector Life Sciences & Health to stimulate public-private partnerships.